Bioinformatics 1 - Mohammed Waheeduddin Hussain (Ukaaz Publications, 2010)
Long DescriptionTHE WORD BIOINFORMATICS IS DERIVED FORM BIOLOGY AND INFORMATICS: THE DISCIPLINE OF BIOINFORMATICS IS RIGHTLY IDENTIFIED AS A COMBINATION OF COMPUTER SCIENCE AND BIOLOGY. IT IS A COMPUTER ASSISTED INTERFACE DISCIPLINE DEALING WITH THE ACQUISITION, STORAGE, MANAGEMENT, AND ACCESS AND PROCESSING OF MOLECULAR BIOLOGY DATA.